Yawning and Penile Erection Frequencies Are Resilient to Maternal Care Manipulation in the High-Yawning Subline of Sprague–Dawley Rats - Dorantes-Nieto, Ángeles; Cortes, Carmen; Ugarte, Araceli; Trujillo Hernández, Angélica; Carrasco, Ángeles; Cepeda-Freyre, Héctor Alejandro; Eguibar, Jose R. (Frontiers in Behavioral Neuroscience, 2020)
Yawning is a stereotyped behavioral pattern characterized by wide opening of the mouth associated with deep inspiration followed by short expiration. All vertebrate species yawn, but with low frequencies. We obtained two sublines of Sprague–Dawley (SD) rats by a strict inbreeding process: one with a high-yawning frequency (HY) of 20 yawns/h, which is one order of magnitude higher with respect to the low-yawning frequency (LY) subline, with 2 yawns/h. Outbred SD rats had a yawning frequency of 1 yawn/h. HY dams had a different organization of maternal care with respect to that displayed by LY and SD dams because HY dams constructed lower quality nests and had more re-retrieving and atypical retrieving. The aim of this study was to analyze the changes in maternal care using in- and cross-fostering between the sublines and SD dams and to measure spontaneous and dopaminergic-induced yawning, penile erections, grooming and scratching bouts. We also measured the expression of dopamine D2 receptors in the striatum using Western blot analysis. Our results showed that HY male rats reared by SD or LY dams did not significantly differ in yawning frequencies with respect to HY male rats reared by mothers of their own phenotype. Maternal care did not differ between sublines and SD dams independent of the litter they reared. However, LY rats reared by HY dams showed a significant increase in the number of spontaneous penile erections. Importantly, in-fostered HY male rats had the highest number of yawns induced by systemic administration of (−)-quinpirole supporting that higher maternal care display can influence the frequency of dopaminergic-induced yawning. In fact HY male rats in all conditions yawned more than did LY and SD male rats independent of the dam that raised them supporting a strong influence of genetic background. However SD male rats raised by LY dams showed significantly increased the dopamine D2 receptor expression. In conclusion, maternal care and the environmental nest conditions during the lactation period did not change the phenotypic characteristics of the yawning sublines supporting that their genetic background is fundamental for the expression of spontaneous or dopaminergic-induced yawning.